The Influence of Charismatic Leadership and Training on The Performance on The Indonesian Navy Hydrographic and Oceanographic Center With Self Efficacy as an Intervening Variable - Indra Dermawan (LPPM Universitas Negeri Jakarta, 2020)
The leadership in the TNI environment is very typical according to the stylish nature of the command organization and is supported by the participation of its members; therefore, this study aims to find out how the influence of charismatic leadership and training on the performance of the Indonesian Navy Hydrographic and Oceanographic Center (Pushidrosal) with Self Efficacy as intervening. This study was conducted on Pushidrosal personnel rank of officers, where the sample used was 217 respondents taken using the census method. Data obtained by questionnaire using a Likert scale to measure 45 indicators processed with Structural Equation Modeling (SEM) using the Amos 22.0 application. The results showed that: Charismatic leadership and training had no direct effect on self-efficacy, self-efficacy had no direct effect on performance. Charismatic leadership and training have a significant positive effect on performance both directly and indirectly. The results of the study also show that Self Efficacy has a positive mediating role for charismatic leadership and training on performance.